COLLECTIVE BENEFITS AS AN IMPULSE FOR URBAN DEVELOPMENT - Czornik, Małgorzata Ewa (Studia Miejskie, 2021)
The development of modern cities is subject to many influences. These include social and cultural inspirations, whose impact results from the local will to adopt new trends, such as the currently popular demands of the postmodern world. Among other things, they promote initiatives intended to integrate urban communities. Cooperation between inhabitants results in the development of urban communities and creation of urban common goods, offering specific types of benefits, such as collective benefits. The purpose of this article is to define and establish the concept of collective benefits substantively among the achievements of urban economy. It has to be stressed that economic relationships which arise in the processes of integrating city users deserve special attention, because the relationships connecting them contribute to the development of unique conditions for living and conducting business. They can be regarded as a broadly understood set of agglomeration economies.